The impact of COVID-19 on chronic pain - Lavin, Abraham; LeBlanc, Félix; El Helou, Antonios (Frontiers in Pain Research, 2023)
A reduced quality of life is often a hefty burden that those with chronic pain are left to bear. This review of literature from PubMed, Google Scholar and other relevant studies focuses on the complex relationship between COVID-19 and chronic pain, which is challenging to study during the COVID-19 pandemic. In this review, we will briefly discuss the epidemiologic facts and risk factors, followed by the proposed pathophysiologic mechanisms. Furthermore, we will cover the therapeutic avenues regarding various molecules and their possible interactions, with the most promising being those whose mechanism of action can be directly linked to the pathophysiologic aspects of the condition. Finally, we will describe how to deal with a chronic pain patient who consults during the pandemic.